2019
DOI: 10.1002/1878-0261.12529
|View full text |Cite
|
Sign up to set email alerts
|

AR splice variants in circulating tumor cells of patients with castration‐resistant prostate cancer: relation with outcome to cabazitaxel

Abstract: The androgen receptor splice variant ( AR‐V ) 7 in circulating tumor cells (CTCs) is a predictor for resistance to anti‐AR‐targeted treatment, but not to taxane‐based chemotherapy in metastatic castration‐resistant prostate cancer (mCRPC). In this study, we investigated whether the presence of two constitutively active variants ( AR‐V3, AR‐V7 ) and two other conditionally activated variants ( AR‐V1, AR‐V9 ) vs full‐length androgen receptor ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Presence of ARV7+ and CTC+ in patients with mCRPC were associated with poorer outcomes on OS along with higher ARV7 values. However, one study reported no significant association with ARV7 [18]. Circulating tumor cells (CTCs) have emerged as a viable solution to the problem whereby patients with a variety of solid tumors, including PC, often do not have recent tumor tissue available for analysis [86].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of ARV7+ and CTC+ in patients with mCRPC were associated with poorer outcomes on OS along with higher ARV7 values. However, one study reported no significant association with ARV7 [18]. Circulating tumor cells (CTCs) have emerged as a viable solution to the problem whereby patients with a variety of solid tumors, including PC, often do not have recent tumor tissue available for analysis [86].…”
Section: Discussionmentioning
confidence: 99%
“…Six studies were observed for the presence of ARVs in CTC. The presence of AR-V9-positive CTCs at baseline in mCRPC was associated with poor survival outcome to cabazitaxel treatment [18], while another study reported no association of AR-V7 with OS on treatment with cabazitaxel [19]. ARV7+ was associated with shorter OS on treatment with androgen-receptor signaling inhibitors (ARSi) [20].…”
Section: Prognostic Biomarkers Androgen Receptor (Ar) Splice Variantsmentioning
confidence: 99%
“…AR-V7 mediates taxane resistance via several mechanisms. Previously, high expression of AR-V7 was linked to NHT resistance, but its expression level declined after chemotherapy (7,8,(16)(17)(18)(19)(20)(21). In recent years, the prognostic value and clinical utility of AR-V7 in NHT and chemotherapy are deeply investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages and disadvantages of AR-V7 detection methods were discussed before (28). Among AR-V7 detection methods, RT-PCR-based tests are the most widely used (12,15,16,20,25,(29)(30)(31)(32)(33)(34). This method is highly sensitive, but its clinical application may be limited because of a defective reliance on the detection of circulating tumor cells (CTCs) and low levels of analytes in liquid biopsy samples.…”
Section: Discussionmentioning
confidence: 99%